2011
DOI: 10.1063/1.3554656
|View full text |Cite
|
Sign up to set email alerts
|

Numerical study of efficiency for a 670 GHz gyrotron

Abstract: In this paper, the results of the efficiency study of a 670 GHz gyrotron operating at TE31,8-mode are presented. Calculations are performed by using the self-consistent nonstationary code MAGY. Three cavity configurations were examined. The effects of ohmic losses and electron velocity spread were included in the simulation. The results show that the output efficiency can reach 35% and the velocity spread in the electron beam does not degrade the operation significantly. Furthermore, we verified that the smoot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
9
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(10 citation statements)
references
References 18 publications
1
9
0
Order By: Relevance
“…The maximum output efficiency 20% was realized at lower currents, in a 57 kV, 16 A operating regime. Taking into account microwave losses in a 3 mm thick teflon window (17-20%) and about 9-10% of ohmic losses of the power radiated in the TE 31,8 -mode one can conclude that the interaction efficiency in this experiment was at about 30% level that agrees with the simulation data [7,8]. The radiated power was converted with the use of standard quasi-optical methods (see, e.g., [9]) into a Gaussian-like wave beam and focused by a teflon lens on the metallic plate with some sharp metallic needle-like breakdown initiators.…”
Section: Resultssupporting
confidence: 85%
“…The maximum output efficiency 20% was realized at lower currents, in a 57 kV, 16 A operating regime. Taking into account microwave losses in a 3 mm thick teflon window (17-20%) and about 9-10% of ohmic losses of the power radiated in the TE 31,8 -mode one can conclude that the interaction efficiency in this experiment was at about 30% level that agrees with the simulation data [7,8]. The radiated power was converted with the use of standard quasi-optical methods (see, e.g., [9]) into a Gaussian-like wave beam and focused by a teflon lens on the metallic plate with some sharp metallic needle-like breakdown initiators.…”
Section: Resultssupporting
confidence: 85%
“…As shown in Ref. 37, when such a gyrotron operates at a high-order mode (such as TE 31,8 ), ohmic losses of radiated power in the circuit walls are relatively small; therefore the output efficiency can exceed 30% at the power level about 300 kW. Among other issues there are a study of production of free electrons by gamma rays, propagation and attenuation of gamma rays, free electrons and THz radiation in air (specifically, in maritime environment), the role of electron diffusion and other processes in air, THz-wave scattering from a small plasma object.…”
Section: Present and Potential Applicationsmentioning
confidence: 71%
“…Taking into account microwave losses in a 2 mm thick teflon window (17%-20%) and about 9%-10% of ohmic losses of the power radiated in the TE 31,8 -mode, one can conclude that the interaction efficiency in this experiment was at about 30% level that agrees reasonably well with the simulation data. 19 The radiated power was converted with the use of standard quasi-optical methods (see, e.g., Ref. 9) into a Gaussianlike wave beam and focused by a focusing mirror on the metallic plate with some sharp metallic needle-like breakdown initiators.…”
Section: -2mentioning
confidence: 99%
“…7 Design of a 670 THz gyrotron operating in this mode 19 showed that the ohmic Q factor of a copper cavity can be as high as 30 000, while the cavity diffractive Q responsible for the outgoing sub-THz radiation does not exceed 3000. So the ohmic losses should be less than 10% of the radiated power, while in devices such as, for example, extended interaction klystron even in the W-band (95 GHz) ohmic losses are at a 1/3 level of the power radiated by an electron beam.…”
mentioning
confidence: 99%
See 1 more Smart Citation